Synthesis, antiviral activity, and molecular docking study of trans-ferulic acid derivatives containing acylhydrazone moiety. Issue 17 (1st September 2017) - Wang, Zhenzhen; Xie, Dandan; Gan, Xiuhai; Zeng, Song; Zhang, Awei; Yin, Limin; Song, Baoan; Jin, Linhong; Hu, Deyu
Graphical abstract: Abstract: In this study, we report the synthesis and antiviral activity of trans -ferulic acid derivatives containing acylhydrazone moiety. Biological tests demonstrated that most target compounds showed potent antiviral activity against tobacco mosaic virus (TMV). CompoundD4 showed remarkable inactivating activity with EC50 value of 36.59 μg/mL, which was obviously superior to ribavirin (126.05 μg/mL). Molecular docking results revealed that compoundD4 exhibited the optimal combining capacity with five hydrogen bonds to different amino-acid residues of TMV coat protein (TMV-CP). Docking results were consistent with the inactivating activity of target compounds against TMV.